Dark plasmonic mode based perfect absorption and refractive index sensing. Issue 26 (22nd June 2017) - Yang, W. H.; Zhang, C.; Sun, S.; Jing, J.; Song, Q.; Xiao, S.
Abstract : Dark plasmonic resonances in metallic nanostructures are essential for many potential applications such as refractive index sensing, single molecule detection, nanolasers etc . Abstract : Dark plasmonic resonances in metallic nanostructures are essential for many potential applications such as refractive index sensing, single molecule detection, nanolasers etc. However, it is difficult to excite the dark modes in optical experiments and thus the practical applications are severely limited. Herein, we demonstrate a simple method to experimentally excite the quadrupolar and higher-order plasmonic modes with normal incident light. By directionally depositing silver films onto the sidewalls of metal-covered one-dimensional grating, we have experimentally observed a series of asymmetrical resonances at the plasmonic ranges of silver gratings. Interestingly, both of the reflection and transmission coefficients of high-order plasmonic modes are reduced to around zero, demonstrating the perfect absorption very well. The corresponding numerical simulations show that these resonances are the well-known dark modes. Different from the conventional dark modes in plasmonic dimers, here the dark modes are the electric oscillations (as standing waves) within the silver sidewalls that are excited by charge accumulation via the bright plasmonic resonance of the top silver strips. In addition to the simple realization of perfect absorption, the dark modes are found to be quite sensitive to the environmental changes. The experimentally measured reflective index sensitivity is around 458 nm per RIU (refractive index unit), which is much higher than the sensitivity of the metal-covered grating without silver sidewalls. This research shall pave new routes to practical applications of dark surface plasmons.